Climate Change and Water Variability : Do Water Treaties Contribute to River Basin Resilience? - Dinar, Shlomi; Katz, David; De Stefano, Lucia; Blankespoor, Brian (World Bank, Washington, DC, 2016)
Climate-driven water variability is a natural phenomenon observed across river basins, but predicted to increase due to climate change. Environmental change of this kind may aggravate political tensions, especially in regions that are not equipped with an appropriate institutional apparatus. This paper argues that attempts to assess the ability of states to deal with variability in the future rests with considering how river basins with agreements have fared in the past. The paper investigates whether basins governed by treaties witness less tension (and by extension more cooperation) over shared water in comparison with those basins not governed by treaties, using the 1948-2008 country dyads event data from the Basins at Risk project. The results provide evidence to suggest that the presence of a treaty promotes cooperation. Furthermore, the number of agreements between riparian countries has a significant positive effect on cooperation, which is robust across different specifications controlling for a broad set of climatic, geographic, political, and economic variables.